Faktor-Faktor Psikologis Yang Mempengaruhi Intensi Membeli Produk Fashion Tiruan - Jazran Efendi; Akhmad Baidun (‎‎‎TAZKIYA Journal of Psychology, 2015)
The aim of the study was to examine psychological factors that predict intention to buy imitation fashoin product. This study used quantitative apporoach by multiple regression with significance level at 0.05. Data were collected from 150 visitors of Tanah Abang shopping center, Central Jakarta, using non-probability sampling. The result showed that there is significance effect of independent variable towards intention to buy imitation fashion product with R2 is 0.334. The test of minor hypotheses showed that motivation to comply has significant effect towards intention to buy imitation fashion product while behavioral beliefs, outcome evaluation, normative beliefs, control beliefs, power of factor and sex have no sginificant effect. Based on the result, consumers are suggested to explore fashion product they want to purchase so they will not get any loss while willing to purchase imitation fashion product. They are also expected to not easily following trends. DOI: 10.15408/tazkiya.v20i2.9177